Pattern recognition receptors and signaling in plant–microbe interactions - Saijo, Yusuke; Loo, Eliza Po‐iian; Yasuda, Shigetaka (The Plant journal : for cell and molecular biology, 2018)
Summary Plants solely rely on innate immunity of each individual cell to deal with a diversity of microbes in the environment. Extracellular recognition of microbe‐ and host damage‐associated molecular patterns leads to the first layer of inducible defenses, termed pattern‐triggered immunity (PTI). In plants, pattern recognition receptors (PRRs) described to date are all membrane‐associated receptor‐like kinases or receptor‐like proteins, reflecting the prevalence of apoplastic colonization of plant‐infecting microbes. An increasing inventory of elicitor‐active patterns and PRRs indicates that a large number of them are limited to a certain range of plant groups/species, pointing to dynamic and convergent evolution of pattern recognition specificities. In addition to common molecular principles of PRR signaling, recent studies have revealed substantial diversification between PRRs in their functions and regulatory mechanisms. This serves to confer robustness and plasticity to the whole PTI system in natural infections, wherein different PRRs are simultaneously engaged and faced with microbial assaults. We review the functional significance and molecular basis of PRR‐mediated pathogen recognition and disease resistance, and also an emerging role for PRRs in homeostatic association with beneficial or commensal microbes. Significance Statement In plants, pattern recognition receptors detect microbe‐associated and host damage‐associated molecular patterns in the extracellular spaces, and thereby trigger intracellular signaling that culminates in an enhanced state of immunity. An increasing inventory of elicitor‐active patterns and their receptors helps us to learn the molecular principles with which plants recognize and deal with a rich diversity of infectious microorganisms, ranging from pathogens, symbionts and commensals, in fluctuating environments.